Nurses' Anxiety amid of COVID-19 Pandemic - Dewi Setyawati; Rasti Sastro; Siti Aisah (University of Muhammadiyah Semarang, 2021)
The psychological response toward pandemics experienced by medical workers is increased due to the anxiety about their health condition and the risk to infect the family member. This research was aimed to describe the nurses’ anxiety amid the COVID 19 pandemic at Piru Hospital. This research was descriptive quantitative research with the cross-sectional approach. The research was conducted from December 29, 2020, to March 4, 2021. The population was 125 medical workers at RSUD Piru, with 95 respondents taken as a sample by using the random cluster sampling technique. The instrument used was Hamilton Rating Scale for Anxiety (HRS-A). The data was then analyzed by using frequency distribution data classified in a table. The result of univariate data analysis showed that 91 respondents (95.8%) didn’t experience anxiety, and 2 respondents (2.1%) experienced anxiety. In case of anxiety, 95.8% of nurses at Piru Hospital in West Seram Regency, Maluku didn’t experience anxiety. The research finding shows the importance of prevention and early detection of anxiety disorder to minimize further impact. Individual identification on the early stage of psychological disorder could be an effective intervention strategy.